A Tree Story - Willis Huston; Carl Keiser (Symphony in the Flint Hills, 2012)
A Tree story as heard by Willis Huston from Carl Keiser, who lived on the blacktop two miles south of Bushong Old timers tell the story about an old elm tree that was the only landmark on the trail between Osage City and Americus , a distance of
Keywords: Lone Elm Tree; Louis Copt; art; story; trees; tree; nature; Bushong; elm tree; Osage City; Mile Creek; Bluff Creek; prairie; fire; grassland; folktale; Willis Huston; Carl Keiser; Americus